Restrictions and Developments: Nahdlatul Ulama Tulungagung under the New Order Policies 1966-1998 - Siska Anggrianto; Fikrina, Alfin Husna (Journal of Islamic History and Manuscript, 2026)
This study examines the forms of restriction and development of Nahdlatul Ulama (NU) in Tulungagung during the New Order era (1966–1998). The New Order implemented various political policies that restricted the movement of Islamic organizations, including bureaucratic politicization, party mergers, surveillance by the security apparatus, and strict regulations in the social, religious, and educational fields. These policies had a direct impact on NU Tulungagung, which experienced administrative discrimination, restrictions on religious activities, pressure on its leaders, and obstacles to the management of educational institutions. The study's results show that, despite various structural and political restrictions, NU Tulungagung did not experience organizational decline. On the contrary, NU demonstrated institutional resilience through adaptation strategies, including shifting the movement's orientation from practical politics to strengthening socio-cultural and educational aspects, adjusting its institutional identity to comply with state regulations, and strengthening its religious base at the community level. These findings confirm that the New Order's repressive policies did not completely weaken Islamic organizations at the local level. The experience of NU Tulungagung shows that the ability to adapt, negotiate, and maintain pragmatic relations with the state was a key factor in keeping the organization's existence amid political pressure. This study is expected to enrich local historical studies and understanding of the relationship between the state and Islamic organizations in Indonesia during the New Order era.